2015
DOI: 10.1037/per0000101
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactivity to social rejection versus a frustration induction among persons with borderline personality features.

Abstract: This laboratory study examined the emotional reactivity of persons with heightened borderline personality (BP) features to a social rejection stressor. Participants with high levels of BP features (n = 43) and controls with low levels of BP features (n = 67) were randomly assigned to a condition involving negative evaluation and social rejection based on personal characteristics, or to a condition involving a frustrating arithmetic task and negative evaluation based on performance. Hypotheses were that the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 58 publications
8
38
1
Order By: Relevance
“…These findings support the hypothesis that negative interpersonal events are stimuli that increase negative affect in BPD (see Carpenter & Trull, 2013; Crowell et al, 2009; Law et al, 2015; Linehan, 1993; Miskewicz et al, 2015), as well as in depressive disorders. They further replicate previous findings on rejection as a predictor for hostility in BPD (Beeney et al, 2014; Berenson et al, 2011; Chapman et al, 2015; Chapman et al, 2014; Renneberg et al, 2012) and augment them by providing similar findings for sadness and fear.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings support the hypothesis that negative interpersonal events are stimuli that increase negative affect in BPD (see Carpenter & Trull, 2013; Crowell et al, 2009; Law et al, 2015; Linehan, 1993; Miskewicz et al, 2015), as well as in depressive disorders. They further replicate previous findings on rejection as a predictor for hostility in BPD (Beeney et al, 2014; Berenson et al, 2011; Chapman et al, 2015; Chapman et al, 2014; Renneberg et al, 2012) and augment them by providing similar findings for sadness and fear.…”
Section: Discussionsupporting
confidence: 86%
“…Previous work has shown a positive relationship between rejection and negative affect, particularly hostility, both broadly (for reviews, see Gerber & Wheeler, 2009; Romero-Canyas, Downey, Berenson, Ayduk, & Kang, 2010) and in BPD participants in particular. For example, compared to non-BPD comparisons, BPD participants and participants high in BPD features reported increased negative affect (Dixon-Gordon, Chapman, Lovasz, & Walters, 2011; Dixon-Gordon, Gratz, Breetz, & Tull, 2013) and hostility (Beeney, Levy, Gatzke-Kopp, & Hallquist, 2014; Chapman, Dixon-Gordon, Butler, & Walters, 2015; Chapman, Walters, & Gordon, 2014; Renneberg et al, 2012) following experimentally induced rejection. Similar findings have been observed using EMA methods: BPD participants reported higher levels of negative affect than healthy controls following two different rejection cues, an interaction partner whom they perceived as acting in a cold-quarrelsome (Sadikaj, Moskowitz, Russell, Zuroff, & Paris, 2013) or a non-communal (Sadikaj, Russell, Moskowitz, & Paris, 2010) way.…”
Section: Introductionmentioning
confidence: 99%
“…In supplemental analyses, we tested the limits of these findings by replacing rejection with perceived criticism, and found that although perceived criticism also predicted increases in GNA, which in turn, predicted greater aggression, this process was not amplified by BPD severity. These results extend prior findings of emotional hypersensitivity to rejection in those with BPD (Berenson et al, 2011; Chapman et al, 2015; Chapman et al, 2014; Gratz et al, 2010), suggesting that increased negative emotional reactivity in the context of rejection, but not criticism, is a potential mechanism underlying women’s aggression that is intensified by BPD symptoms after accounting for comorbid ASPD symptoms.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, based on previous studies suggesting heightened negative emotional reactivity to rejection in those with BPD or elevated BPD symptoms (Berenson et al, 2011; Chapman, Dixon-Gordon, Butler, & Walters, 2015; Chapman et al, 2014), we hypothesized that this indirect within-person effect would be intensified among women with greater BPD symptoms after controlling for overlapping ASPD symptoms. Specifically, as depicted in Figure 1, we predicted:…”
Section: Aims and Hypotheses Of The Current Studymentioning
confidence: 99%
“…Further, BPD features are associated with ruminative response deployment following interpersonal rejection, but not in response to a film-based sad mood induction (Napolitano et al, 2018). In a similar vein, couples have been shown to ruminate when one member of the dyad interpersonally withdraws from the other (King & DeLongis, 2014), a stressor for which those with BPD have a heightened sensitivity (Chapman, Dixon-Gordon, Butler, & Walters, 2015;Peters, Smart, & Baer, 2015;Renneberg et al, 2012).…”
Section: Interpersonal Context and Ruminationmentioning
confidence: 97%